Impact of COVID-19 Pandemic on Science Learning at Secondary Level - Teotia, Anil Kumar (SCHOOL SCIENCE, 2020)
Science is suffering from potential loss, and this is going to be very costly. Science learning is being compromised due to strict stay-at-home orders and school closures for Indian students. In this article, the researcher tried to investigate the effect of COVID-19 on the teaching and learning of science (particularly at the secondary level) in India's schools and educational institutions. The thought of online teaching and learning may sound exciting to many, but to science lovers, it is not! Students seem to dislike science with online classes because the essential elements of science classes are absent in online classes. Moreover, this may affect the future scientists of the nation. Additionally, access to technology, strict time tables, and teachers' inability to adapt to this online culture can be considered the main hurdles in teaching science in online mode. Further, the researcher has also elaborated on the point of online lectures and virtual labs. Somehow, this pandemic may end up helping us to address the improper science assessment policies too.